A nano-micro structure engendered abrasion resistant, superhydrophobic, wearable triboelectric yarn for self-powered sensing. (1st December 2022) - Chen, Weichun; Fan, Wei; Wang, Qi; Yu, Xichen; Luo, Yu; Wang, Weiting; Lei, Ruixin; Li, Yi
Abstract: Smart wearable electronics with harvest energy are rapidly developing in modern life. Fiber-based triboelectric generators (TENGs) are gaining extensive attention for energy harvesting and human motion sensing, due to flexible, lightweight, and comfortable properties. However, it is difficult to coordinate the high electrical output performance of fiber-based TENGs with the requirements of human wearing comfort (abrasion resistant, air permeability and skin-friendliness). Herein, a novel nano-micro structure yarn (NMSY) with three layers was proposed via combining conjugated electrospinning as well as ring spinning together. Therein, electrospinning Nylon 11 nanofibers were applied as the intermediate layer to enhance electrical output performance and ring spinning polyester fibers wrapped as the outermost layer to improve abrasion resistance. The obtained NMSY exhibits high output voltage (17.5 V in 3.5 cm) and wear resistance (4500 abrasion cycles). Furthermore, an electronic textile (e-textile) was knitted with NMSY (2.5 × 2.5 cm 2 ), which exhibited a power density of 487.8 mW/m 2 at a load resistance of 700 MΩ. Owing to the unique interconnected loop structure of knitted textiles, NMSY e-textile shows good air permeability (147.3 mm/s), water vapor transmission rate (3470 g/(m 2 ·24h)) and excellent skin-friendly. In practical application, NMSY e-textile can lit up 22 LEDs and also can charge the commercial capacitors efficiently. Besides, NMSY as well as the corresponding e-textile can also be used as self-powered sensors to monitor body movement. In summary, the superior NMSY presented in this work could enhance energy harvest and wearability, which would pave the way toward full-fledged commercialization of the TENGs in the future. Graphical Abstract: A nano-micro structure triboelectric yarn is used for self-powered sensing and energy harvesting. Owing to the nano-micro structure, NMSY exhibits superior abrasion resistance and electrical output performance for human practical application. Besides, the NMSY e-textile can be woven into the knitted textile with wear resistance, super-hydrophobicity, air permeability, water vapor permeability and skin affinity. Furthermore, the presented fabrication that combines electrospinning and ring spinning would pave the way toward full-fledged commercialization of the TENGs in the future. ga1 Highlights: The obtained yarn has high abrasion resistance and electrical output performance. High performance yarn has an output voltage of 17.6 V in 3.5 cm. The e-textile shows high output power density of and good wearing comfort. This work may pave the way toward full-fledged commercialization of the TENGs.